Teoría morfogenética y pensamiento de los grupos sociales - Mansilla, Matías (2025)
The morphogenetic approach is a theoretical perspective developed by the English sociologist Margaret Archer. Combining elements from the relational sociology with others coming from critical-realist philosophy, the morphogenetic approach results in a theory that little by little has expanded from its birthplace, England, to the rest of the world. In this work, I propose to think the formation of social groups from the morphogenetic approach, searching to highlight or contribute useful concepts for the elaboration of a theoretical framework in this line. For this, I will recover the contributions from Archer and Frédéric Vandenberghe. The last one, a great contributor to the study of groups in the frame of the presented theory. Thus, I will use, principally, the concepts of reflexivity and avatars of the collective developed by Archer and Vandenberghe respectively. Starting from these concepts, I will tackle the question for the processes that could lead to the formation of social groups and the formation of its capacity for collective action. I will finish proposing the concept of shared reflexivity as one that can contribute to explain both the aforementioned processes and the categories or social classifications involved in the same.